2015
DOI: 10.1097/ccm.0000000000001249
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Infection in the Critically Ill, a Multicenter Study of Molecular Detection in Bloodstream Infections, Pneumonia, and Sterile Site Infections*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 29 publications
3
132
1
2
Order By: Relevance
“…Lately, a PCR/electrospray ionization-mass spectrometry (PCR/ ESI) technology was developed to detect more than 800 bloodstream infection-relevant bacterial and Candida species within 6 h of sample acquisition. Findings from the RADICAL study showed 81% sensitivity, 69% specificity, and 97% negative predictive value with PCR/ESI when compared with conventional cultures [74]. In a set of prospectively collected blood samples in sepsis patients, PCR/ESI and standard microbiology were concordant in 86% of culture-positive samples [75].…”
Section: What Are Remaining Areas Of Uncertainty? Invasive Candidiasismentioning
confidence: 93%
“…Lately, a PCR/electrospray ionization-mass spectrometry (PCR/ ESI) technology was developed to detect more than 800 bloodstream infection-relevant bacterial and Candida species within 6 h of sample acquisition. Findings from the RADICAL study showed 81% sensitivity, 69% specificity, and 97% negative predictive value with PCR/ESI when compared with conventional cultures [74]. In a set of prospectively collected blood samples in sepsis patients, PCR/ESI and standard microbiology were concordant in 86% of culture-positive samples [75].…”
Section: What Are Remaining Areas Of Uncertainty? Invasive Candidiasismentioning
confidence: 93%
“…A study involving 616 BSIs and 185 pneumonia cases tested the PlexID ™ platform, which is able to detect 800 relevant pathogens. The system identified 55 of the 68 positive blood cultures, but was also positive in 173/625 of negative blood cultures [8]. The interpretation and therapeutic implications of recovering positive PCR in the absence of positive microbial culture remain debated.…”
Section: Rapid Diagnostic Tests For Selecting Adequate Antimicrobialsmentioning
confidence: 99%
“…Beginning with blood culture collection, there is growing interest and success in direct-from-blood pathogen detection assays. Some progress has already been made in this domain, including SeptiFast [4], IRIDICA [5], and T2 Biosystems [6], although only the last is FDA cleared, and only for detection of Candida species. A MASTERMIND protocol for direct-from-blood pathogen detection could theoretically collect enough blood from each enrolled subject to submit for multiple test evaluations (Figure 3), though required volumes may sometimes be limiting and may not enable a large number of diagnostics to be run on a single specimen.…”
Section: Mastermind Study Possibilitiesmentioning
confidence: 99%